Mammalian sialyltransferases allow efficient Escherichia coli-based production of mucin-type O-glycoproteins but can also transfer Kdo. (22nd December 2021) - Sim, Lyann; Thompson, Nicole; Geissner, Andreas; Withers, Stephen G; Wakarchuk, Warren W
Abstract: The prospect of producing human-like glycoproteins in bacteria is becoming attractive as an alternative to already-established but costly mammalian cell expression systems. We previously described an Escherichia coli expression platform that uses a dual-plasmid approach to produce simple mucin type O-glycoproteins: one plasmid encoding the target protein and another O-glycosylation machinery. Here, we expand the capabilities of our platform to carry out sialylation and demonstrate the high-yielding production of human interferon α2b and human growth hormone bearing mono- and disialylated T-antigen glycans. This is achieved through engineering an E. coli strain to produce CMP-Neu5Ac and introducing various α-2, 3- and α-2, 6 mammalian or bacterial sialyltransferases into our O-glycosylation operons. We further demonstrate that mammalian sialyltransferases, including porcine ST3Gal1, human ST6GalNAc2 and human ST6GalNAc4, are very effective in vivo and outperform some of the bacterial sialyltransferases tested, including Campylobacter jejuni Cst-I and Cst-II. In the process, we came upon a way of modifying T-Antigen with Kdo, using a previously uncharacterised Kdo-transferase activity of porcine ST3Gal1. Ultimately, the heterologous expression of mammalian sialyltransferases in E. coli shows promise for the further development of bacterial systems in therapeutic glycoprotein production.